Analysis of emotional vocabulary in Korean (based on TOPIK texts) - Muazzamova, Zuhra (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
The article analyzes the semantic structure, grammatical use and significance of emotional words in the cultural context. The main attention is paid to the expression of emotions in the speech culture of the Korean language, and it is shown what pragmatic functions these words perform in speech. The role and significance of emotional vocabulary in the language learning process are explained based on examples found in TOPIK exams.